Food and Activities Taboos among Sundanese Pregnant Women - Mira Trisyani Koeryaman; Kim Hee Kyung; Restuning Widiasih (Faculty of Nursing Universitas Padjadjaran, 2019)
Taboos are found everywhere including Indonesia. There are different types of taboos in Indonesia especially during pregnancy. This study aimed to identify the practice of taboos related to food and activities among Sundanese pregnant women in West Java, a province with the largest population. A cross-sectional study was conducted with 312 pregnant women, who come to antenatal care at maternal and child health clinics of hospital, health care center and private midwifery clinics at four districts area in West Java province (Cianjur, Bandung, Sumedang and Garut) from October–December 2014. The data were selected purposively used the questionnaires included important demographic characteristics and questions regarding food and activities taboos during pregnancy. SPSS Win.12.0 were used for data analysis. The practice of food and activities taboo among pregnant women showed were about 29.4% very often, 42.1% often, 22.4% rarely, and 6.1% never in avoid to eat certain foods and to do particular activities during pregnancy. No statistically significant association was found between food and activities taboo during pregnancy and data demographics of respondents (p>.05). Still often done by pregnant women in avoid to eat certain foods and restriction to do particular activities. To assess the true picture we need to conduct larger studies in the community with interview method. These findings would be an important information for nurses in developing health education in maternal periods, and considering women’s culture and beliefs in nursing care plan.